Industrialization and employment : with special reference to Asia and the Far East - Mehta, Madhava Mal. (Bombay : Popular Prakashan, 1976)
The author attempts to examine in the light of historical and analytical reasoning the feasibility and practicability of bringing about a more labor-intensive technology-mix without compromising the overall rate of industrial growth in labor- surplus and capital-deficient countries of Asia and the far East. Approximately one half of the book is devoted to a Statistical Supplement consisting of twenty-two tables, the data-sources dating from 1963-1969. The ECAFE countries analyzed in the study include Taiwan, India Republic of Korea, Pakistan, Philippines, Thailand and Japan.
Includes bibliographical references.
rpm 17/04/2018
Loans
Keywords: Labor supply; Manpower policy; Industrialization; India